Proactive outcome monitoring and standardisation of physiotherapy stroke rehabilitation - A retrospective functional outcomes analysis of Accelerated Stroke Ambulation Programme (ASAP) - Bryan Ping Ho Chung; Titanic Fuk On Lau (World Scientific Publishing, 2023)
Background: A clinical quality improvement programme named Accelerated Stroke Ambulation Programme (ASAP) was piloted in Physiotherapy Department of Tai Po Hospital from 1st October 2019 to 30th September 2020 and executed as a standard practice afterwards. The goal of ASAP was to facilitate early maximal walking ability of stroke patients in early rehabilitation phase. ASAP featured (1) proactive outcome monitoring and standardised process compliance monitoring by a patient database - Stroke Registry; (2) standardised mobility prediction by Reference Modified Rivermead Mobility Index (MRMI) Gain and (3) standardised intervention database - Stroke Treatment Library. Objective: To investigate the effectiveness of ASAP in an inpatient rehabilitation setting for stroke patients in terms of functional outcomes. Methods: The design was a retrospective comparative study to analyse the difference in functional outcomes of Pre-ASAP Group (1st October 2018 - 30th September 2019) and Post-ASAP Group (1st October 2020-30th September 2021). The primary outcome measures were MRMI, Berg's Balance Scale (BBS), Modified Barthel Index (MBI), MRMI Gain, BBS Gain, MBI Gain, MRMI Efficiency, BBS Efficiency and MBI Efficiency. Results: There 348 subjects in Pre-ASAP Group and 281 subjects in Post-ASAP Group. Both groups had highly significant within-group improvement in MRMI, BBS and MBI ([Formula: see text]). The MRMI Gain of Pre-ASAP Group and Post-ASAP Group was 6.32 and 7.42, respectively; and the difference was significant ([Formula: see text]). The BBS Gain of Pre-ASAP Group and Post-ASAP Group was 8.17 and 9.70, respectively; and the difference was in margin of significance ([Formula: see text]). The MBI Gain of Pre-ASAP Group and Post-ASAP Group was 10.69 and 11.96, respectively; but the difference was non-significant ([Formula: see text]). The MRMI Efficiency, BBS Efficiency and MBI Efficiency of Post-ASAP Group were higher than Pre-ASAP Group but the difference was non-significant. The results of this study reflected that stroke rehabilitation programme with proactive outcome monitoring, standardised process compliance monitoring, standardised mobility prediction and standardised intervention database was practical in real clinical practice with better functional outcomes than traditional physiotherapy practice which were dominated by personal preference and experience of therapists. Conclusion: Proactive outcome monitoring, standardised process compliance monitoring, standardised mobility prediction and standardised intervention database may enhance the effectiveness in terms of functional outcomes of stroke rehabilitation programme.